Preservation of ecosystems of international watercourses and the integration of relevant rules an interpretative mechanism to address the fragmentation of international law by - Lee, Jing (International water law series, 2014)
In Preservation of Ecosystems of International Watercourses and the Integration of Relevant Rules: An Interpretative Mechanism to Address the Fragmentation of International Law, Lee Jing takes an innovative approach to developing an international legal framework for preserving ecosystems. Deploying Article 31(3)(c) of the 1969 Vienna Convention an analytical approached is devised that examines 'the ecosystem approach' under international law through the prism of Article 20 of the UN Watercourses Convention.